2005
DOI: 10.1111/j.1365-2133.2005.06752.x
|View full text |Cite
|
Sign up to set email alerts
|

High local interleukin 5 production in granuloma faciale (eosinophilicum): role of clonally expanded skin-specific CD4+ cells

Abstract: that GPs find it difficult to recognize skin cancer and prioritize referrals. Limited urgent capacity is filled with routine referrals at the expense of delaying detection of skin cancer from nonurgent referrals. Dermatologists must therefore pay particular attention to nonurgent referrals to ensure that these referrals are assigned equal priority.In summary, skin cancers are referred urgently and nonurgently by GPs. The urgency assigned to the referral influences the waiting time. Administrative streamlining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…[10] In addition, an increased production of IL-5, probably induced by the clonal expansion of a locally recruited T-cell population may enhance the attraction of eosinophils into the lesions of GF. [11] Therefore, a possible mechanism of action of topical tacrolimus in this condition may be the inhibition of IFN-gamma and IL-5 production and release, induced by the down-regulation of the T-cell activity, primarily involving the calcineurin binding and inactivation. However, we did observe eosinophils in skin biopsy in our case, probably since the biopsy was taken after one year of oral dapsone.…”
Section: Discussionmentioning
confidence: 99%
“…[10] In addition, an increased production of IL-5, probably induced by the clonal expansion of a locally recruited T-cell population may enhance the attraction of eosinophils into the lesions of GF. [11] Therefore, a possible mechanism of action of topical tacrolimus in this condition may be the inhibition of IFN-gamma and IL-5 production and release, induced by the down-regulation of the T-cell activity, primarily involving the calcineurin binding and inactivation. However, we did observe eosinophils in skin biopsy in our case, probably since the biopsy was taken after one year of oral dapsone.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous report also suggested that topical administration of tacrolimus ointment increased the number of IL-10 producing cells and enhanced the production of TGF-β [11]. Regarding GF, Gauger et al [12] previously reported that increased levels of IL-5 in the lesional skin might contribute to the pathogenesis of GF. In our present case, indeed, the eruption diminished after 2 months of topical administration of 0.1% tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…58 A local IL-5 production by T cells most likely contributes to eosinophil infiltration. 59 Eosinophilic granulomatosis with polyangiitis (Churg-Strauss syndrome)…”
Section: Granuloma Facialementioning
confidence: 99%